The regulation of miR-155 strand selection by CELF2, FUBP1 and KSRP proteins - Jeff S. J. Yoon; Thomas C. Chamberlain; Nada Lallous; Alice L.-F. Mui (Scientific Reports)
Abstract The microRNA-155 exists in two forms, miR-155-5p and miR-155-3p, produced from either strand of the double-stranded precursor of miR-155 in a mutually exclusive manner. The more abundant and better-studied miR-155-5p has been implicated in numerous biological processes, with dysregulated expression observed in various human diseases. miR-155-5p plays an essential role in supporting inflammatory responses in macrophages. Activating macrophages with lipopolysaccharide (LPS) elevates miR-155-5p, while the anti-inflammatory cytokine interleukin-10 (IL10) reduces miR-155-5p levels. Recently, researchers have suggested that miR-155-3p also plays a role in macrophage function, although its specific function in this context remains unclear. We found that LPS stimulation of macrophages results first in the elevation of miR-155-3p levels, followed by an increase in miR-155-5p levels. In this paper, we investigate the mechanisms underlying the maturation of pre-miR-155 into either miR-155-5p or miR-155-3p. We describe the contribution of three RNA-binding proteins, CELF2, FUBP1 and KSRP, to pre-miR-155 processing. Our data suggest that CELF2 regulates the selection of miR-155-5p and miR-155-3p strands. FUBP1 may support the expression of miR-155-3p for specific subcellular functions, while KSRP appears to inhibit both miR-155-5p and miR-155-3p maturation without altering the relative expression of each strand.